PKM Pelatihan Pembuatan Media Promosi Menggunakan Aplikasi Adobe Photoshop di Toko Fasha Muslim Cibinong - Haikal, Muhamad; Khotijah, Siti; Driyani, Dewi; J, Juliana (Yayasan Daarul Huda Kruengmane, 2025)
The development of the digital era brings both challenges and opportunities for micro–business owners in expanding their enterprises. One of the main challenges lies in their ability to adapt to digital technology within marketing activities. Toko Fasha Muslim, a business engaged in producing Muslim women’s apparel such as gamis, hijabs, tunics, kebayas, Muslim socks, and mansets in the Cibinong area, has so far relied primarily on traditional marketing methods. Therefore, this community service activity was carried out in the form of a training program on creating digital advertisements using Adobe Photoshop software. The main objective of this program is to enhance employees’ skills in designing attractive and effective product advertisements capable of reaching a wider market. The training began with an introduction to the basics of Photoshop, image editing techniques, and continued to the creation of professional advertisement designs. The results of the training showed a significant improvement in participants’ ability to produce more creative visual promotional content that aligns with current digital market trends. Thus, this activity is expected to help Toko Fasha Muslim expand its marketing reach and increase its competitiveness amid the growing digital–based business landscape.